DEVELOPMENT OF SOCIAL RESPONSIBILITY OF NON-MILITARY EDUCATIONAL STUDENTS - Uzoqov Akrom Avazovich (American Journals Publishing, 2022)
Currently, our state gives the National Personnel preparedness a lot of attention. Conditions are being established for the advancement of science, widespread participation of gifted youth in scientific endeavors, and the fulfilment of their intellectual and creative potential. More than 300 years ago, the scientific foundation for Project Education started to be established. German educator, According to Knoll's research, the idea of "project" emerged in the 16th century at a period when Italian architects began to regard the discipline of architecture as a science, systematizing the scientific underpinnings of the profession. This article offers feedback and input on how non-military school students are growing in their social responsibility.
Keywords: conscription, military education, students, Development, Social, Responsibility, activity, process.